Correlation of GLUT4, LEPR , and TNF-a with endometrial receptivity in women with polycystic ovarian syndrome-induced infertility - Yan Dong; Kong Wei; Yifei Li; Yan Liu; Lin Li; Yan Li (Journal of Medical Biochemistry)
Background: To analyze the correlation of glucose transporter 4 (GLUT4), leptin receptor (LEPR), and tumour necrosis factor-a (TNF-a) with endometrial receptivity (ER) in patients with polycystic ovarian syndrome (PCOS)induced infertility to provide clinical evidence for future diagnosis and treatment of PCOS-induced infertility. Methods: We prospectively enrolled 109 study subjects admitted to The Second Hospital Affiliated of Shandong University of Traditional Chinese Medicine from June 2020 to August 2023, including 42 patients with PCOS-induced infertility (research group), 35 nonpregnant patients with simple PCOS (control group), and 32 nonpregnant healthy women (normal group). GLUT4, LEPR, and TNF-a levels in the peripheral blood were detected in all participants, and their diagnostic value for PCOS in healthy women and PCOS-induced infertility in PCOS patients was analyzed. In addition, the endometrial thickness and endometrial blood flow pulsation index (PI) and resistance index (RI) of patients in the research group were measured. Furthermore, the correlation of GLUT4, LEPR, and TNF-a with ER was discussed. Results: GLUT4 was lower in the research group compared with the control and normal groups, while LEPR and TNFa were higher (P<0.05); the control group showed lower GLUT4 and higher LEPR and TNF-a levels than the normal group (P<0.05). The diagnostic sensitivity and specificity of GLUT4, LEPR, and TNF-a combined assay for PCOSinduced infertility in PCOS women were 88.57% and 75.00%, respectively, and those for PCOS in healthy women were 78.57% and 60.00%, respectively (P<0.05). In the research group, GLUT4 was positively correlated with endometrial thickness and negatively linked to RI and PI. At the same time, LEPR and TNF-a were negatively associated with endometrial thickness and positively correlated with RI and PI (P<0.05). Conclusions: GLUT4, LEPR, and TNF-a are closely related to ER in patients with PCOS-induced infertility, and their combined detection can effectively evaluate the occurrence of PCOS and PCOS-induced infertility.